Utilização da lignina como aditivo antienvelhecimento em ligantes asfálticos - Rafael Antônio de Lima Neto (2022)
One of the major infrastructure problems in Brazil is related to the quality of the asphaltic pavements. The country is extremely reliant on road transport and since it is one of the largest countries in the world, in relation to territorial extension, it has one of the longest road networks worldwide. A study that is of great interest to the country’s economy and for the safety and comfort of the population is based on the research for new additives that can improve the general properties of the asphalt, reducing its ageing and making it a more resistant material in the face of heavy traffic and inclement weather. The lignin is a byproduct of paper and pulp industry that is, in addition to being abundant, still very underused and is has been widely tested as a modifier for asphaltic binders, due to its antioxidant properties. The oxidation, alongside with the exposure to ultraviolet radiation from the sun, is one of the factors that impact the most on the ageing and degradation of the pavement. This work aims to evaluate the effects of lignin addition in different concentrations on the consistency and on the physical properties of the asphaltic binder through characterization, viscosity and elastic recovery tests. The samples produced were submitted to ageing on RTFOT, which simulates the ageing on mixing process, and on weathering chamber, which simulates the ageing during the pavement service life, when exposed to UV radiation, moisture, and temperature variations. After, it was performed analysis with Fouriertransform infrared spectroscopy (FTIR) and rheological analysis with a dynamic shear rheometer (DSR) to comprehend the effects of lignin in the molecular structure and in the elastic behavior of the binder after the ageing processes. The tests suggested a beneficial effect of the addition of Kraft lignin against asphalt oxidation and it also increased the elasticity of the material and its resistance to plastic deformations.